Analisis Dinamika Penelitian Pencemaran Air Sungai berdasarkan Studi Bibliometrik 10 tahun terakhir - Mia Erpinda; Nur Faizaturrohmah; Suci Wulandari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This study analyses the research dynamics on river water pollution over the last decade (2014-2024) using bibliometric analysis. Data were collected using Publish or Perish software with Google Scholar as the main source, using keywords such as 'river pollution', 'river water quality', 'river contamination' and 'river water pollution'. Articles published between 2014 and 2024 were selected, resulting in a total of 1,000 relevant publications. The bibliometric analysis was conducted using VOSviewer version 1.6.20, which allowed mapping of research trends and visualisation of key themes through network, overlay and density visualisation. The results identified five major clusters in river pollution research, with three dominant themes: